Conditioning and updating under cumulative prospect theory - Alex Stomper; Marie-Louise Vierø (Queen's University, Department of Economics, 2009)
This paper derives conditions under which the well-known decomposition of unconditional expected utility into marginal probabilities and conditional expected utility generalizes to Cumulative Prospect Theory, as well as updating rules for probability weighting functions. The results are, for example, of interest for empirical and experimental work, when available choice data is for situations where payoffs given the conditioning events are random.
Keywords: 330; Probability Weighting Functions; Cumulative Prospect Theory; Conditioning; Updating; Prospect Theory; Wahrscheinlichkeitsrechnung; Mathematische Ökonomie